Iluzje obecności. Cielesność w Bez końca Krzysztofa Kieślowskiego - Kulessa, Kamila (Przestrzenie Teorii, 2019)
This paper aims at providing an analysis of Krzysztof Kieślowski’s film No end (1984), focused mainly on representations of corporality. The article attempts to interpret possible meanings of the phantasmatic dimension of existence and its impact on the reality constructed in the film. It also examines issues related to identification and the articulation of sensuous presence in cinematic images.